Summer outbursts in the coma of comet 67P/Churyumov–Gerasimenko as observed by Rosetta–VIRTIS. Issue 1 (18th August 2018) - Rinaldi, G; Bockelée-Morvan, D; Ciarniello, M; Tozzi, G P; Capaccioni, F; Ivanovski, S L; Filacchione, G; Fink, U; Doose, L; Taylor, F; Kappel, D; Erard, S; et al.
ABSTRACT: We present an analysis of transient events observed by the Visible InfraRed Thermal Imaging Spectrometer, instrument aboard Rosetta, for the dates of 2015 August 10, September 13 and 14, during the two months surrounding the comet perihelion passage of the Rosetta spacecraft. We detected and characterized events with life-times ranging from 26 min down to 6 min. The temporal evolution of the outburst shows a sudden increase of radiance from quiescent coma to the maximum in a few minutes. This rapid onset is correlated with a change of the visible dust colour from red, 15–18± 3 ${{\ \rm per\ cent}}$ /100 nm, to bluer with values of 7–10± 0.3 ${{\ \rm per\ cent}}$ /100 nm. The dust morphology of these outbursts can be classified into two main types: narrow and collimated plumes (August 10, September 13) and broad blobs (September 14). The observations suggest that there are localized regions on the surface that are more prone to outbursts than the rest of the nucleus. The projected dust velocity during the outburst events ranges between 22.2 ± 2.2 m s −1 and 64.9 ± 10.6 m s −1 . The total ejected mass during an outburst event is estimated to be between 10 and 500 tons for a duration of 6–26 min assuming size distribution indices between −2.5 and −3.